Neural Representation of Parental Monitoring and Links to Adolescent Risk Taking - Lee, Tae-Ho; Qu, Yang; Telzer, Eva H. (Frontiers in Neuroscience, 2019)
Decades of developmental research have demonstrated the positive role of parental monitoring during adolescence, a time during which youth seek exploration and show heightened risk taking. The present study employed a novel neural pattern similarity approach to identify neural patterns underpinning parental monitoring, with attention to implications for adolescent risk taking. Mothers (N = 23) underwent an fMRI scan during which they completed a risk-taking task and viewed the risk-taking behavior of their adolescent child. Using a representational similarity analysis, we examined the neural pattern similarity between mothers’ anticipation of their child’s risk taking and their own decisions. Higher parental monitoring was reflected in greater similarity between neural pattern of anticipating their adolescents’ risk taking and experiencing their own safe outcomes. Moreover, greater neural pattern similarity between mothers’ anticipation and their own safe outcomes was associated with lower risk-taking propensity in adolescents. Taken together, the present study provides preliminary evidence for the neural patterns underpinning parental monitoring, highlighting the importance of incorporating parents’ brain as a window to understand parenting practices and adolescent risk taking.